PRODUK FERMENTASI RUMEN SAPI POTONG SECARA IN VITRO YANG DIBERI PAKAN SILASE DAUN NANAS SEBAGAI PENGGANTI RUMPUT GAJAH - Saputro, Alif Rizki Tixko; Suhartati, Fransisca Maria; Rimbawanto, Efka Aris (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. This study aims to examine the effect of using pineapple leaf waste silage as a substitute for elephant grass based on levels of Nitrogen-ammonia (N-NH3) and Volatile Fatty Acid (VFA) concentration in total rumen fluid of beef cattle in vitro. The research was conducted from August 25 to September 20, 2022 at the Laboratory of Nutrition and Animal Feed Science, Faculty of Animal Science, Jenderal Sudirman University, Purwokerto. Materials and methods. The study using an in vitro method with a completely randomized design, 5 treatments and each treatment was repeated 4 times so that there were 20 research units. The treatments used consisted of P0 (60% concentrate + 40% elephant grass), P1 (60% concentrate + 30% elephant grass + 10% pineapple leaf silage), P2 (60% concentrate + 20% elephant grass + 20% pineapple leaf silage), P3 (60% concentrate + 10% elephant grass + 30% pineapple leaf silage), and P4 (60% concentrate and 40% pineapple leaf silage). Results. The results showed that the treatment had no significant effect (P>0.05) on the levels of N-NH3 and the concentration of VFA. Conclusion. It was concluded that the use of pineapple leaf silage at a balance of 40% elephant grass and 60% concentrate could replace elephant grass in beef cattle feed up to 100% based on in vitro measurements of N-NH3 levels and total VFA concentrations.